Training in Language Switching Facilitates Bilinguals’ Monitoring and Inhibitory Control - Liu, Cong; Yang, Chin-Lung; Jiao, Lu; Schwieter, John W.; Sun, Xun; Wang, Ruiming (Frontiers in Psychology, 2019)
In the present study, we use a training design in two experiments to examine whether bilingual language switching facilitates two components of cognitive control, namely monitoring and inhibitory control. The results of Experiment 1 showed that training in language switching reduced mixing costs and the anti-saccade effect among bilinguals. In Experiment 2, the findings revealed a greater decrease of mixing costs and a smaller decrease of the anti-saccade effect from pre- to post-training for the language switching training group compared to the second language training group. Overall, the results suggest that extensive exercise in monitoring and inhibitory control in an experimental setting may enhance the corresponding components of cognitive control. We discuss these findings in the context of the relationship between bilingual language control and executive control.